Interactive effect of stress state and grain size on fracture behaviours of copper in micro-scaled plastic deformation. (March 2019) - Li, W.T.; Li, H.; Fu, M.W.
Abstract: To explore the interactive influence of the deformation stress state and material microstructural grain size on the fracture behaviour in micro-scaled deformation, a series of micro-scale copper specimens of various geometrical dimensions and microstructural grain sizes are prepared and deformed to achieve various stress states represented by stress-related variables, such as the normalised third deviatoric stress invariant and the stress triaxiality. The speckle pattern method of continuous tracking is used to investigate the mechanical responses of materials in various deformation stress states and material microstructures, and a finite-element simulation of each deformation is conducted with the combined surface layer and grain boundary strengthening constitutive model, which considers the contributions of the surface grain, grain interior and grain boundary in representing the grain and geometry sizes. The interactive effects of the normalised third invariant, stress triaxiality and microstructural grain size on the fracture strain are identified and established by accounting for the correlation between the results of simulation and those of physical experimentation. Their influences on the fracture mechanism, mode and behaviour are further explored. The results reveal that greater stress decreases the fracture strain in the tensile deformation of round bar and cylindrical compression and increases the fracture strain in sheet shear and tensile deformations. The larger grain size generates fewer micro-voids, more uneven grain distribution and severer localisation deformation, which accelerates failure. Furthermore, stress triaxiality and the normalised third invariant at a low stress triaxiality are decreased with the increase of grain size, which in turn affects the occurrence of fracture. These effects coexist and compete with each other. In view of these influences, a larger grain size and a higher stress state inhibit the occurrence of fracture for sheet specimens with fracture modes from shear-dominant to dimple-dominant; in contrast, a smaller grain size and a lower stress state inhibit the occurrence of fracture in other cases. Highlights: Interactive effect of stress state ( η, ξ ) and grain size d on ductility is studied. Decrease in d and stress triaxiality η impedes failure occurrence in bar tension. Reduction in d, η and the normalised invariant ξ increases ductility in compression. Increase in d, η and ξ prevents fracture formation in sheet shear and tension. Fracture mechanism, mode and behaviour are affected by d, η and ξ .